A Comparative Study on Contract-Based and Coproduction-based Entrepreneurship Training Programs: A Study Case of Jakarta Province - Hassan, Fazlur Rahman; Anandhika, Muhammad Rizqy; Izzi, Maulana Fajrul (UI Scholars Hub, 2023)
Training is essential to guide and equip SMEs with the necessary skill sets to adapt to the disruption of the COVID-19 pandemic. The budget limitation urged DKI Jakarta Provincial Government (DJPG) to change their conventional training program for SMEs and arrange an IT-based platform enabling all city entities, including private and non-private sectors, to participate in a coproduction scheme. This study employed the performance outcomes framework to examine the impacts of coproduction in entrepreneurship training for SMEs by comparing contract-based and coproduction-based training conducted by DJPG, including the impacts on the deliverables and budget. The results indicate that overall, coproduction-based training is proven to be more efficient, effective, and flexible than contract-based training. This study suggests that coproduction-based training programs deserve to be allocated a significant portion of the government entrepreneurship training agenda while maintaining essential contract-based training programs to ensure the continuity of the government budget in this field.